The effectiveness of a six-week selective rotary exercises program on the spatial and temporal gait parameters in elderly men - Mojtaba Babaei Khorzoghi (Tehran University of Medical Sciences, 2020)
Background & Aim: With age, some physiological changes cause a negative effect on gait patterns. The aim of this study was to evaluate the effectiveness of a 6-week rotary exercises program on spatial and temporal gait parameters in elderly men. Methods & Materials: This was a quasi-experimental study. A total of 38 employees and retirees over 60 years of age from Isfahan University of Technology in 2019, were selected by the convenience and purposeful sampling and were randomly divided into experimental and control groups (19 people). The gait parameters were assessed through marking the subjects' trunk and lower extremities, along with simultaneously filming from three directions (anterior, posterior, and lateral) with a Canon 700D camera, and loading the videos into KINOVEA software. The exercise program were performed in three 60-minute sessions per week for six weeks. To analyze the data, descriptive statistics and the analysis of variance with repeated measures were used. Results: The results showed a significant difference in the number of steps per minute (Cadence) (P<0.001), step speed (P=0.019), stride time (P<0.001), step time (P<0.001), time of stretching or deployment (P=0.002), oscillation time (P<0.001) and dual protection time (P=0.014), but other parameters such as stride length (P=0.102), step length (P=0.137) and step width (P=0.089) were not significantly different. Conclusion: Implementation of the 6-week combined rotary exercises program in the elderly can improve the gait parameters, reduce the risk of falls and thus reduce the number of referrals to treatment centers in this age group.